Vilniaus gubernijos atmintinės knygelės kaip informacijos šaltinis - Briliūtė, Salvinija; Matulaitytė, Stasė (Knygotyra, 1983)
In 1835 in Vilnius was established a statistical committee the function of which was to collect and systematize statistic data about the province of Vilnius, its inhabitants, productive forces etc. In order to acquaint the society with these data it was decided to publish annually Information directories. This “Памятная книжка Виленской губернии” (1845–1915) has been an important source of information on historic, factual, statistic data of the city of Vilnius and its province. The structure of the book has changed in the course of time. The publication consisted of one or two books and several chapters in which the were presented lists of employees in various institutions of the province, a calendar, adresses, various information, statistical and some other matter, literary and historical articles on the Lithuanian history, etnography, archeology, historical and architectural monuments. education, medical service, etc. The article reveals the circumstances under which the publication emerged, its internal life. changes in its structure and contents depended on many circumstances even on the editors of the book and the collaborators of the editing committee. In the article there is presented the estimation of the published material is interesting to a contemporary reader and scientist.